Analysis of the pipe conveyor belt pressure on the rollers on its circuit. (May 2016) - Barburski, Marcin
Conveyor belts are widely used in almost all industries, agriculture and construction. They are made of fabric and rubber carcass and rubber covers. Pipe conveyor belts are a relatively new technology in comparison to the conventional conveyor belts, as they offer many advantages and additional features. However, one of the main problems concerning pipe conveyor belts and appearing at the close of the belt is the collapse of the edges inward. This causes gaping of the belt, which may result in a loss of material being carried. The main purpose of the performed study was to develop a new woven structure which would restrict the undesirable effect of collapsing the edges of the pipe conveyor belt inward. To achieve the main objective, it was pre-determined, how the weave influences the piping of the belt. Nine fabrics of different weaves were made with polyester warp and polyamide weft. New position was built as part of the research to measure the pressure of piped belt on a set of rollers located on its circuit. Analysis of the results allowed development of the new woven structure with a variable rigidity on the belt width. In one woven fabric three different weaves were used symmetrically to its longitudinal axis. The study of the newly designed belt showed that it has better closing properties and that the effect of collapsing the edges inward was eliminated.